Penyuluhan penanganan panen dan pasca panen padi gogo di Desa Pollewani, Kecamatan Tubbi Taramanu, Polewali Mandar: Extension services on upland rice harvesting and post-harvest handling in Pollewani Village, Tubbi Taramanu Subdistrict, Polewali Mandar - Ikrar Taruna Syah; Rahmaniah HM.; Rahmawati Ning Utami (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Polewali Mandar Regency comprises 16 sub-districts, with the most significant administrative area being Tubbi Taramanu Sub-district, which is one reason this region remains less